(untitled) (Minerva, 2020)
Supplementary to the previous paper published by Julián Solana Pujalte in Minerva 29 (2016) 269-301, this article deals with the books in Greek in the historical library located in the Colegio de la Asunción (Córdoba, España) and focuses on their topics, dates, printing places, printers, owners and reading.